Experiences of genetic testing among individuals with retinitis pigmentosa. (3rd September 2022) - Krauss, Emily; Macher, Jared; Capasso, Jenina; Bernhardt, Barbara; Ali-KhanCatts, Zohra; Levin, Alex; Brandt, Rachael
ABSTRACT: Background: Retinitis pigmentosa (RP) is a genetically heterogeneous retinal dystrophy which results in progressive vision loss. There is scant literature on the experiences of genetic testing in patients with RP. Materials and Methods: Patients with a clinical diagnosis of RP who received genetic testing at the Wills Eye Ocular Genetics clinic between 2016 and 2020 were recruited. Telephone interviews were conducted using a semi-structured guide designed to elicit participant experiences with genetic testing. A thematic analysis was performed to describe patterns in participant responses. Results: Twelve patients participated. Seven participants identified as female and five as male, with ages ranging from 22 to 70. Ten patients had positive genetic test results, while two had negative genetic testing. Reported motivations for genetic testing included qualification for clinical trials (58% of total participants), determination of etiology or usal gene (50%), reproductive concerns (50%), and prognostic outlook (50%). Most participants (75%) expressed satisfaction about their decision to pursue genetic testing. Participants with both positive and negative genetic testing reported persistent uncertainty regarding their prognosis for visual decline (50%). Genetic confirmation of disease leads to initiation of safety and vision-protecting health behaviors (42%). Conclusion: Patients with RP are generally satisfied with their testing experience, despite approaching testing with a wide range of motivations and expectations. Future research can leverage this methodology to identify targets for improvement in pre- and post-test education and counselling.